C3H6N6 doping effect of synthetic diamond under high pressure and high temperature. (February 2020) - Wang, Junzhuo; Li, Shangsheng; Hu, Meihua; Su, Taichao; Gao, Guangjin; Guo, Mingming; You, Yue; Nie, Yuan
Abstract: In this paper, large diamond crystals were successfully synthesized under 5.6 GPa at temperature 1513 and 1553 K with melamine (C3 H6 N6 ) additive. Fourier transform infrared spectroscopy (FTIR) indicated C3 H6 N6 is an ideal nitrogen source for large diamond crystal synthesized by temperature gradient method (TGM), but its hydrogen is not absorbed by diamond. With the increase of C3 H6 N6 content, the colour of diamond changed from yellow to green, and the highest nitrogen content of diamond is 2300 ppm. High synthesis temperature can effectively reduce the formation of defects and play a key role in the formation of C-centers during diamond growth. Surprisingly, diamond is likely to grow into twin crystal when the C3 H6 N6 content is 0.1 wt%. In the process of diamond growth, carbon atoms of C3 H6 N6 are likely to serve as carbon source to form plane dislocations, which eventually lead to the formation of twin diamond. Raman spectra show that there are few crystal defects in diamond synthesized with C3 H6 N6 as dopant. Highlights: Nitrogen content of diamond synthesized with C3 H6 N6 as dopant reaches 2300 ppm while ensuring crystal quality. Twin diamonds were synthesized with 0.1 wt% doping of C3 H6 N6 under 5.6 GPa. This is the lowest synthetic pressure for the twin diamonds at present.